Gema Kriya di Tengah Jagad Budaya - Sugiharjanto, Asto Adi; Toekio, Soegeng (KEMADHA, 2011)
Indonesia as an archipelagic country as well as a maritime nation that is rich in customs and lush islands in bantangan equator . The country also recognize the diversity in cultures and ethnic groups scattered. Indigenous culture that was born of the tribes in many cases the common feature would also imaging, including a wealth of material culture is very diverse. When the concept of blown art complements the realm of science and technology, his position became increasingly taken into account. Many efforts and tips to find novelty in the concept and engineering of this material. One phenomenon which is currently less preached, is the existence kekriaan as one kind of Indonesian art In the atmosphere created by dualism mainstream of the developing nations, will require many wise minds to be able to form a renewal without any cultural conflict. Negative picture of the atmosphere that can only be a source of catastrophe for the existence of cultural assets that no longer have a place to exist. However , it does not mean that the old habits that rests on peradatan was then terluluhkan. Actually there are superior power of indigenous culture (ethnicity) and has a strong desire to keep strong in the midst of a global culture. Excellence that has been proven true history has shown its reputation and acknowledged able to appear in the middle of chess world. Some of them would not even be something that is familiar , such as: batik, wayang, gamelan, keris / tosanaji, weaving, plaiting, grabah, and other kria products that use natural ingredients.Similarly, wide opportunities to enter the constellation of global culture, but it is very unfortunate that the impact of multi-cultural arena that makes the attitude of complacent. Theres homework to explore the local idioms become a source of knowledge that was valid and the accelerated nature of arena global.Dari rich repertoire of such kekriaan it is possible to tampil. Beside that, the sources of art in the barn and spread culture, still only in conditions hardly budge.Exposure is inclined to open a portion of the map kekriaan which allows to be explored to further packed into bertara information science. Like a pearl that has not been honed, the sources kekriaan will put the validity of the archipelago when art idiom be appointed as part of the taxonomy of art.